Etika Profesi Hukum: Mengungkap Pelanggaran Kode Etik dalam Kasus Suap Pengacara - Eizeluna Farnesty; Fenny Rahma Sari; Raihan Dzaky; Rani Bela Septia; Siti Balqis Alayya; Syifa Maura Adinda; Vina Khalisa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The legal profession in Indonesia carries significant responsibility in upholding justice, particularly through adherence to the Indonesian Advocates Code of Ethics (KEAI). However, violations of this code, such as bribery involving lawyers, often undermine the integrity of the judicial system. This study examines how ethical breaches, particularly in bribery cases, occur and their impact on the legal profession and public trust in the judiciary. Using a normative juridical method, the study focuses on analyzing legal norms that regulate lawyers' conduct, including relevant legislation. Cases such as those involving lawyers Lucas and Fredrich Yunadi highlight how these violations influence court decisions and undermine the principles of justice. The findings reveal that factors such as client pressure and weak oversight from professional organizations contribute to bribery violations. This practice not only damages public trust in the legal profession but also threatens the integrity of the judicial system, which is expected to operate fairly and transparently. Therefore, comprehensive efforts are required to prevent ethical violations, including strengthening oversight, enforcing strict sanctions, and enhancing ethics education for future lawyers.